(untitled) (Research, Society and Development, 2022)
Introduction: The word functional food can be described as any material/ingredient used as food to help prevent disease or improve quality of life. Pineapple is a perennial plant, belonging to the Bromeliaceae family, much appreciated in producing regions and in importing countries, due to its aroma and flavor characteristics, maintaining a balance between sugar and acidity. Pineapple peel is an input not valued in the food industries, which can help in the human diet in a complementary way. This study aims to disclose the characterization of pineapple and its peel, presenting its properties through a narrative review. Methodology: For the survey of scientific articles in the literature, a search was carried out through the online databases of the VHL, SCIELO, Science Direct, MEDLINE, LILACS and PMC, UFRGS, UFPA, SEBRAE, and Google School in English, Spanish and Portuguese. Portuguese. Results and discussions: The chemical composition of pineapple varies mainly according to the time of year in which it is generated, its diversity and the atmospheric conditions, it has energy value, and high composition of sugar and nutritional value due to the presence of mineral salts (calcium , phosphorus, magnesium, potassium, sodium, copper and iodine) and vitamins (C, A, B1, B2 and Niacin). Conclusion: Bromelain is a proteolytic enzyme found in pineapple that shows anti-inflammatory, antitumor, aids in food digestion, anti-thrombosis, burns and mucolytic effects.